Use of an acoustic telemetry array for fine scale fish behaviour assessment of captive Paiche, Arapaima gigas, breeders. (22nd April 2018) - Núñez‐Rodríguez, Jesús; Vela Díaz, Antonia; Bazan‐Albitez, Roger; Rebaza Alfaro, Carmela; Koua, Daniel; Núñez, Lucie; Testi, Baptiste; Renno, Jean‐François; Duponchelle, Fabrice; Pella, Hervé
Abstract: As Arapaima gigas is one of the most valuable species for the growing production of Amazonian aquaculture, knowledge of its reproductive behaviour and its application to increase reproduction success in captivity is of great importance as no hormonal spawning induction technique exists for this species. An acoustic positioning system (LOTEK Inc.) was used to observe the interactions of adult fish to better understand the formation of mating pairs. Fish were placed in a 4, 500 m 2 aquaculture pond over a 6‐month period in the IIAP field station of Pucallpa, Perú. This paper describes the methodological protocols used to set up and test the hydrophone array and presents the methodology used for the analysis of the huge amount of collected data. This methodology is illustrated by the analysis of a 6‐day period for a mating pair that showed a spawning event. The results indicated that male and female occupied mostly one preferential area in one pond edge where the nesting area is located. Different activity patterns were observed during the spawning event, with male and female being closer during the spawning day. The results also showed that male travelled less distance than female during the studied period. Finally these results demonstrated the suitability of such equipment to monitor fish interactions at fine spatial (sub meter) and temporal (5 s) scales in confined environments like aquaculture ponds.